Peran Dinas Pemberdayaan Perempuan dan Perlindungan Anak Kota Makassar Dalam Mewujudkan Pemenuhan Hak-hak Anak - Novayanti Sopia Rukmana; Asmaul Husna (Universitas Negeri Makassar, 2023)
Abstract: This study aims to determine the role of the Empowerment Office Women and Child Protection of Makassar City in Realizing The fulfillment of children's rights is seen from the role as coordinator, facilitator, and Stimulator. This type of research is qualitative which is descriptive with Data collection techniques are carried out by observation, interviews and documentation. The results of this study show that the role of the Empowerment Office Women and Child Protection Still Not Good. Especially on indicators from The role of the Women's Empowerment and Child Protection Office as The coordinator is strategic prevention and protection of the fulfillment of children's rights It hasn't completely gone well, that is, there are still some children who experiencing conflicts, not going to school or dropping out, not being recorded, and Untouched by the Government.Keywords: Makassar, Women, dan Children